Carcinoma em tumor misto da mama da cadela: avaliação de aspectos morfológicos e perfil imunofenotípico - Gustavo Meirelles Ribeiro (2010)
Mammary tumors in dogs are frequent neoplasms and carcinomas respresent for 50% of all. The carcinoma in mixed tumor in dogs is frequent and is composed by malignant epithelial elements (in situ and invasive) and benign mesenquimal elements. The aim of this study is to describe morphological findings in canine carcinoma in mixed tumor and classify them like human patterns, also identify the immunophenotypical profile of those carcinomas using a immunohistochemical markers and correlate the morphological and immunophenotypical characteristics. Descriptive analysis of 29 cases of carcinoma of mixed tumor was done to investigate morphological features, estimating histological grade and histological type of in situ and invasive elements in carcinomatous component. For mesenchimal component we estimated the frequency of mixoid and chondromixoid matrix and mesenquimal elements (cartilage, bone and bone marrow) as well. The immunohistochemical study included: hormone receptors (ER and PR), human epidermal growth factor receptor 2 (HER2), cytokeratin 5 (CK5) and epidermic growth factor type I receptor (EGFR). Carcinoma in mixed tumor in female dogs showed morphological features very similar to the metaplasic carcinoma of human breast. All tumors showed mixoid or chondro-mixoid matrix in mesenquimal component besides elements like cartilage (13.8%), cartilage/bone (10.3%) and cartilage/bone/bone marrow (10.3%). The epithelial component showed histological grade I in 55.2% of cases, histological grade II in 34.5% of cases and histological grade III in 1.5% of cases. The most frequent histotype of malignant epithelial component in situ was Solid. Immunophenotypically, invasive malignant epithelial component showed more frequency of luminal A (41.4%) followed by basal-like (27.6%) subtypes, no statistical significance was observed with histological grade (p=0.735). There was statistical significance on the immunophenotypical profile of malignant epithelial component in (situ and invasive) (Kappa coefficient=0.816; p<0.01). We concluded that carcinoma in mixed tumor in dogs show tissue components very similar to metaplasic carcinoma of human breast, but discordant features in relation of histological grade and immunophenotypical profile. These data suggest that additional studies are needed on clinical and pathologycal characteristics of canine mammary tumors in order to use it like model for compared pathology.